The Essence of Applying Modern Methods in Education - Pardayeva Dilfuza Ravshanovna (International Journal on Orange Technologies, 2022)
The main form of organization of the educational process is the lesson and requires the introduction of various non-traditional forms of the lesson. This condition develops the creative ability of the student, strengthens his mental capacity, expands his worldview, and develops the skills and abilities to quickly and fully accept any innovation. This article presents scientific conclusions about the organization of the modern educational process in the development of science and technology, the results of teaching methods.